STRATEGI PENGEMBANGAN DESA WISATA AAN KECAMATAN BANJARANGKAN KLUNGKUNG - Desak Made Purnama Dewi; I Made Gede Darma Susila; I Made Suwitra Wirya (Universitas Triatma Mulya, 2022)
A tourism village is a community consisting of residents of a limited area who can interact directly with each other under management and have awareness and awareness to play a role together by adapting different individual skills. Tourism villages are formed to realize the community so that they can act as direct actors in an effort to increase readiness and awareness in responding to tourism potential or tourist attractions in the area of each village. This study aims to formulate a development strategy for the tourism village of Aan as a tourism destination in Klungkung. Aan Village has enormous potential but faces a number of obstacles in its development. This is indicated by the diversity of tourism potentials originating from nature, culture and man-made tourist attractions. The research was conducted through a qualitative descriptive analysis using SWOT analysis to find strategies for developing the potential of the Aan tourism village and tourism area life cycle analysis. Data collection techniques through observation, in-depth interviews, documentation and literature study. Retrieval of informants was done by purposive sampling. The results of the study show that to maximize the development of the attractiveness of Aan Village as a tourist destination, it is necessary to develop strategies and programs such as community empowerment, development of supporting infrastructure, and collaboration with stakeholders and the private sector in creating sustainable programs